(untitled) (Medico Legal Update, 2020)
Assessment of depression among the housewives of alcohol consuming husbands in selected community areas, Kancheepuram District, Tamil Nadu. Aim of the study is to Assessment of depression among house wives. The objectives are to determine the level of depression among house wives of alcohol consuming husband, to find out the association between the level of depression with their selected demographic variables of the house wives of alcohol consuming husband.169 samples are selected by purposive sampling techniques. Data collected by using Beck’s Depression scale. The data collected period was for one week. The collected data was tabulated and analyzed. Descriptive and inferential statistical were used. The results are majority 53% of house wives having depression and Minority 47% of house wives did not having depression. Assessment of demographic variables regard to Factors associated with the level of depression among the demographic variables, Family type,family monthly income ,Frequency of consuming alcohol,Variables like Age,Educational status of wife, Educational status of husband, Employment status of husband,Problem after alcohol consumption,Physically abuse after consumption of those Demographic variables doesn’t has significant association.